2017
DOI: 10.1111/voxs.12398
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from Paris and Nice

Abstract: terrorists committed several attacks in Saint-Denis and the East Parisian districts. These attacks, claimed by the organization Islamic State, constitute the deadliest series of multisite attacks that France has experienced. The stake for the Etablissement Franc ßais du Sang (EFS, the French public blood service) was to face the shockwave that propagated throughout the whole establishment from the very minutes following the events, impacting all the processes and stakeholders involved in the transfusion chain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Effective communication during MCEs is critical. It is common for many more blood components to be requested than are eventually transfused, and the overall requirement for products in these events is often lower than expected . Most blood use in MCEs occurs within the first 24 hours, particularly in the first 4 hours as the majority of severe casualties arrive within this time frame .…”
Section: Discussionmentioning
confidence: 99%
“…Effective communication during MCEs is critical. It is common for many more blood components to be requested than are eventually transfused, and the overall requirement for products in these events is often lower than expected . Most blood use in MCEs occurs within the first 24 hours, particularly in the first 4 hours as the majority of severe casualties arrive within this time frame .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of transfusion requirements following the attacks in Paris and Nice revealed that patients who required blood transfusions received a mean number of 4-8 RBC units in Paris and 3-7 RBC units in Nice as well as a mean number of 4 units of FFP and 0-4 units of platelets in both Paris and Nice [45]. Whether the percentage of patients receiving blood products, nor the range of the overall need were shown in detail.…”
Section: Theoretical Need For Blood Products In a Mass-casualty Terromentioning
confidence: 99%
“…A recent increase in mass casualty events from gun violence and terrorism has led to discussion on how health care teams should prepare for these disasters. [61][62][63][64][65][66] In large mass casualty events analyzed from 1980 to 2016, the 75th percentiles for units transfused per admission were 3.9 units of RBCs, 3.6 units of plasma, and 0.48 platelet doses. Most blood products were needed within the first 12 to 24 hours (medians: RBCs, 67%; plasma, 75%; platelets, 84%).…”
Section: Transfusion Approaches To Hemorrhagic Shock and Mass Casualtiesmentioning
confidence: 99%